Evaluation of geomorphic expressions of bedrock Channels in the Western Ghats of southern Kerala, India, through quantitative analysis - Hamza, Vijith; Prasannakumar, V.; Pratheesh, P.; Krishnan, M.; Mohan, M. (Springer, 2016)
Geomorphic expressions embedded within the bedrock channels, originating from the southernmost part of the Western Ghats, India, are quantitatively characterized through well-defined geomorphic indices using digital elevation models (DEM) and geographical information system (GIS) tools. Drainage basin asymmetry (Af), transverse topographic symmetry factor (T), longitudinal profile, stream length gradient index (SL), hypsometric integral and curve (Ihyp), spatial parameters like drainage density (Dd) and dissection index (DI) are used for extraction of information related to the characteristic pattern and behaviour associated with the Karamana river and its two major tributaries. The independent and cumulative analysis of each geomorphic indices indicates adjustment of Karamana river in response to the tectonic activities. Karamana basin, while showing symmetric character as a single unit, exhibits segments of asymmetric nature associated with the terrain tilting and is evidenced from the variable directional oscillation from E, SSE, S, NW and W. Varying characteristics of the longitudinal profiles and abrupt change in the SL index suggest knick points and uplift of the terrain due to tectonic processes. The influence of tectonic process over the stream characteristics is confirmed by identifying higher levels of SL anomalies in unique lithology. The inferences correlate with the low drainage density and high dissection index zones in the region with varying influence of tectonic processes. Though, the Karamana river basin as a single unit shows old age characteristics in the hypsometric analysis and symmetric nature, the longitudinal profile-assisted SL and SL anomaly indices are found to be capable of revealing evidences of differential effects of tectonic activities over the stream characteristics. The deductions are in agreement with field observations on landforms and channel attributes.